PENGARUH SUMBER DAYA MANUSIA, KOMITMEN ORGANISASI, PEMANFAATAN TEKNOLOGI INFORMASI, PENGAWASAN KEUANGAN DAERAH DAN PENGENDALIAN INTERN AKUNTANSI TERHADAP KEANDALAN PELAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN SOLOK SELATAN - Anggreini Permata Sari; Yuneita Anisma; Rofika ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The research was aimed to test the influence human resource, comitmen organization, information technology utilization, local financial monitoring, and accounting intern control to reliability of financial reporting Solok Selatan regency. This research is motivated by the fact that the government financial reporting should provide information on reliable and timely in assessing accountability and decision making of various parties. All variables in this research were measured using a likert scale.The data in this study is the primary data obtained from questionnaires distributed directly to the respondents.Data collected from 57 respondents who are working at financial reporting staff in SKPD of Solok Selatan regency. The collected data was processed using SPSS 23 version with multiple linier regression. The results of research is showed that human resources, comitmen organization, utilization of technology, local financial monitoring, and internal accounting control influence to the reliability of financial reporting in Solok Selatan regency.Based on the calculation of the coefficient of determination (R2) obtained a value of 0,535. This shows that the influence of the independent variables in the dependent 53,5% and the remaining 46,5% influenced by other variables.Keywords : Human resource , comitmen organization, information technology utilization, local financial monitoring, and reliability financial